(untitled) (Research, Society and Development, 2021)
Objective: experience report of nursing students regarding the performance of rapid anti-HIV tests, as well as the confrontation of results and user counseling. Methodology: this is a descriptive study with a qualitative approach, of the type of experience report, lived by four students and one teacher, during the practical activities, in April 2019. Results and discussion: six rapid anti- HIV, with a positive result. For the performance of rapid tests it is necessary to perform the correct technique, the use of Personal Protective Equipment (PPE) indispensable in any assistance, good communication between team professionals and network professionals, as well as advice efficient pre and post-test. The dissemination, dissemination and performance of rapid tests in the population, ended up having a purpose of guidance and monitoring of the user, empowering him to be the protagonist of his health, despite this being still a deficiency in assistance. Conclusion: the experience of a positive result caused a change of vision and thoughts, where it is expected that there is a need for networking, with the availability of multiple professionals for comprehensive and effective care.